ISLAMIC MARKETING MANAGEMENT DALAM SOCIETY 5.0 - Risyatul Azkiya; Khuzaini; Syahrial Shaddiq (PT. Saha Kreasi Indonesia, 2025)
The rapid development of technology has brought significant changes in the world of business and management, including marketing practices. The concept of Society 5.0, initiated by Japan, represents the era of a super-smart society where digital technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), big data, and robotics are utilized to improve human life quality. In this context, Islamic Marketing management plays a strategic role in directing business development while maintaining Islamic values and ethical standards. This study aims to explain the concept of Islamic Marketing Management in facing the challenges of the Society 5.0 era and how Sharia principles can be integrated into technology-based marketing strategies. This research uses a qualitative approach with a literature study method from various sources, including books, scientific journals, and previous studies. The findings indicate that Islamic Marketing Management emphasizes not only consumer satisfaction but also justice, honesty, transparency, and blessings in transactions. The application of Islamic values in digital marketing serves as a strong foundation for achieving a sustainable and ethical economy amidst technological advancement.